2008
DOI: 10.1590/s0100-72032008001000006
|View full text |Cite
|
Sign up to set email alerts
|

Amenorréia e anormalidades do cromossomo X

Abstract: GioRGio adRiano Paskulin 7 Artigos originaisResumo ObjetivO: correlacionar as manifestações clínicas de pacientes com amenorréia e anormalidades do cromossomo X. MétOdOs: realizou-se uma análise retrospectiva dos achados clínicos e laboratoriais das pacientes com amenorréia e anormalidades do cromossomo X, atendidas entre janeiro de 1975 e novembro de 2007. Suas medidas antropométricas foram avaliadas através de tabelas de crescimento padrão, sendo que, quando presentes, dismorfias menores e maiores foram anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In the literature, CAs associated with SA have been described to mainly affect the X chromosome, 9 a finding that accords with that of our study reporting that among patients with CAs, 85.7% had abnormalities involving the X chromosome. In our sample, the main alteration involving the X chromosome was the deletion of parts of its long arm, which corresponded to 21.4% of the CA cases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the literature, CAs associated with SA have been described to mainly affect the X chromosome, 9 a finding that accords with that of our study reporting that among patients with CAs, 85.7% had abnormalities involving the X chromosome. In our sample, the main alteration involving the X chromosome was the deletion of parts of its long arm, which corresponded to 21.4% of the CA cases.…”
Section: Discussionsupporting
confidence: 92%
“…CAs described in association with SA can be numeric or structural, and they can occur in an isolated form or involve more than one cellular lineage. 6 , 9 Furthermore, these patients generally exhibit a wide range of phenotypic abnormalities, other clinical features, and hormonal profiles. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical phenotype was not completely compatible with the described features of triple X females (Butnariu et al, 2013). The array-CGH test was essential for defining the break points and showed that although she indeed had 3 copies of SHOX (Xp22.33), which may explain her high stature (180 cm), she had only 1 copy of FOP1 (Xq28), a gene related to premature ovarian failure, which may have caused her hypogonadism hypogonadotropic (Rosa et al, 2008). Eighteen CNVs were classified as probably causative (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Common hormonal cause of primary amenorrhea includes pituitary dysfunction, chronic systemic disease, and absent ovarian function. [2] Hyperprolactinemia is associated with decreased estradiol concentrations and amenorrhea. Prolactin concentrations are high in women with amenorrhea.…”
Section: Introductionmentioning
confidence: 99%